Do berço ao porvir: o fracasso escolar e a estruturação psíquica precoce - uma articulação entre educação e psicanálise - Nolasco, Vivian (2019)
The present study, which is bound by Educational Policies Research, aims to investigate the hypothesis of education failure from students who are related to an earlier aspect in their school entry and that concerns to the lifetime marks from the early days of constitution, a decisive factor for the human development, thought and intelligence: the early psychic structuring. It acomplishes a clipping of multiple causes that can affect school difficulties and then go deeper into those that are the product of failures in structuring and that can be confused with a lack of intellectual capacity and learning problems. Based on the hypothesis of failures in early psychic structuring, and by means of theoretical and conceptual articulation between Sociology of Education and Psychoanalysis, it reviews the literature, it implemets a concept theory confrontation and an intersection between two theories - the Cultural Capital, stemming from the Sociology of Education, and the Psychical Early Structures, from Psychoanalysis - with the intention of reaching a plausible inference about the causes of school failure. The psychoanalytic theoretical framework was mainly developed from the contributions of Freud, Lacan, Laplanche, Winnicott, Bleichmar, A. Jerusalinsky, J. Jerusalinsky, and Laznik. The questions related to the sociology concepts were anchored at the studies of Bourdieu, Lahire, and Charlot. The study has shown that early psychic structuring may be one more constraint layer to school failure . The methodology used in this research is exploratory in relation to the objectives, and bibliographical in terms of procedures. The study revealed that early psychic structuring may be one of the conditioning factors for school failure, as failures in the prim ordial motherbaby relationship generate problems in setting thought and intelligence processes up. This research also found that lags in the academic and continuing education of professionals in day care centers and nurseries, caused by the absence of psychoanalytic references that should guide and support the necessary actions for structuring, are blocking the professional to detect and intervene in time and preventivily attempt to avoid the installation of lags, and to refer to treatment those babies who are suffering. Based on this conclusion, it is necessary to implement an educational policy for educators undergraduate education and continuing education based on the theory of early psychic structuring.